2012
DOI: 10.3126/hren.v10i2.6570
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological patterns of ovarian tumors at BPKIHS

Abstract: Introduction: Ovarian tumors account for fifth most common cause of cancer related death in females involving a variety of histological diagnosis. It accounts for 6% of all cancers. Though it is one of the treatable cancers due to its sensitivity to anticancer therapies, it frequently does not result in symptoms until the cancer has spread extensively. Objectives: To study the incidence, histopathological spectrum and clinical correlates of ovarian tumours at B.P. Koirala Institute of Health Sciences (BPKIHS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 24 publications
9
23
1
Order By: Relevance
“…In our study, the most common ovarian tumours were Surface epithelial tumours comprising 74.06%, followed by Germ cell tumours comprising 15.82% and Sex cord stromal tumours comprising 10.12%.Similar observations were made by Swami and Satyanarayana 9 , Gupta et al 10 and Pradhan A et al 11 The most common epithelial tumour were Serous cystadenoma followed by Mucinous cystadenoma and most common Germ cell tumour was benign cystic teratoma seen in 15 cases. Similar results have been reported by Yasmin et al 12 In our study the most common complaint of patients was lump in abdomen in 88 cases (85.7%) followed by pain in lower abdomen, about 70 cases (44.3%).These findings are in concordance with those of a study carried out by Pradhan A et al…”
Section: Discussionsupporting
confidence: 77%
“…In our study, the most common ovarian tumours were Surface epithelial tumours comprising 74.06%, followed by Germ cell tumours comprising 15.82% and Sex cord stromal tumours comprising 10.12%.Similar observations were made by Swami and Satyanarayana 9 , Gupta et al 10 and Pradhan A et al 11 The most common epithelial tumour were Serous cystadenoma followed by Mucinous cystadenoma and most common Germ cell tumour was benign cystic teratoma seen in 15 cases. Similar results have been reported by Yasmin et al 12 In our study the most common complaint of patients was lump in abdomen in 88 cases (85.7%) followed by pain in lower abdomen, about 70 cases (44.3%).These findings are in concordance with those of a study carried out by Pradhan A et al…”
Section: Discussionsupporting
confidence: 77%
“…Age range of our patients was from 9 years to 65 years and the mean age was 36.58 ±10.45 years. Mean age of our study was similar to other study 1,5,6,7 . In the present study we found a higher percentage of non-neoplastic lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Incidence of ovarian cancers is increasing and it is an important cause of cancer deaths in women in our country. The survival rate is low due to absence of effective tumor markers, screening protocol and the disease seldom produces symptoms before getting complicated or huge size 1,2 . Early diagnosis is important for better management of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian malignancies constitute about 25% of malignant tumours of the female genital tract. [1][2][3][4] The incidence of ovarian carcinoma is greater in high income countries compared to middle and low income countries. In 2012, approximately 239,000 cases were recorded, which account for nearly 4% of all new cases of carcinoma in women (2% overall).…”
Section: Introductionmentioning
confidence: 99%
“…Around the world, the incidence rate of ovarian carcinoma is 11 per 100,000 in Central and Eastern Europe, 5 per 100,000 in Africa, 11.7 per 100,000 in the US, 5.2 per 100,000 in Brazil, and 4.1 per 100,000 in China. 2 In India, the ovarian cancer incidence (age-adjusted rate per 100,000) in different population-based cancer registries is reported to range from 1.7 to 15.2 for the year 2012 to 2014. An increasing trend of this cancer has been observed since 1982 to date.…”
Section: Introductionmentioning
confidence: 99%